Evaluating learning technologies: frameworks and case studies. (10th August 2006) - Scanlon, Eileen; Blake, Canan; Issroff, Kim; Lewin, Cathy
Evaluation frameworks have been developed for studying learning technology. In this paper, we review their application to a number of evaluation projects, reflect on recent developments in the area of evaluation and illustrate how these frameworks have been applied by reflecting on the methods employed in three contrasting case studies. Each case study is an evaluation of an innovative use of information technology. The first case study describes the evaluation activities related to the technology-enhanced components of an introductory physics course for distance learners, 'Physical World', focusing on the evaluation of multimedia tutorials. The second case study discusses an evaluation project focusing on the impact of networked technologies on learning at school level, the 'ImpaCT2' evaluation, and describes the methods used in tracking use of technology both at school and at home. The third case study involves the evaluation of a history website on a full time higher education course, 'The History of the USA'.